Exploring Teachers’ Multimodal Pedagogy Practices: Leveraging Visual Resources in English Classroom - Indah Purnama Dewi; Evi Karlina Ambarwati; Praditya Putri Utami; Tedi Purbangkara (Universitas Muhammadiyah Enrekang, 2024)
Research Background: English language education has evolved significantly in recent decades, especially with the increasing use of visual resources in teaching. The use of visual resources such as images, videos, and infographics has become an integral part of modern pedagogy, known as multimodal pedagogy. This research was conducted to understand how teachers utilize visual resources in their teaching practices in English classrooms. Research Objective: This study aims to explore and document multimodal pedagogical practices used by English teachers in utilizing visual resources to enhance students' learning experience. Research Method: This research uses a qualitative approach with a case study method. Data were collected through classroom observation, in-depth interviews with teachers, and analysis of teaching documents. Observations were made at several junior high schools in major cities, and interviews were conducted with ten experienced English teachers. Research Results: The results show that teachers use a variety of visual resources to support their teaching. The use of relevant images and videos helps students understand the subject matter better. In addition, infographics and visual sketches are used to explain complex concepts. Teachers also incorporate digital technologies such as multimedia presentations to make learning more interactive and engaging. Research Conclusion: This study concludes that the use of visual resources in multimodal pedagogy practices is very effective in increasing students' understanding and involvement in the teaching and learning process. Teachers who use this strategy succeed in creating a more dynamic and interactive learning environment, which ultimately improves student learning outcomes.